Legal Framework on Women’s Participation in Legislative Elections in Indonesia: A Normative Analysis of the Role of Political Parties - Guterres, Mirela Maria Ribeiro; Dewi, Anak Agung Sagung Laksmi (CV WAHANA PUBLIKASI, 2025)
Women’s participation in legislative elections is one of the key indicators of the success of substantive democracy in Indonesia. The Indonesian Constitution guarantees equality between men and women in all aspects of state life. However, women’s representation in legislative bodies remains far below expectations, despite the existence of several legal regulations governing quotas and women’s participation in politics. This article examines two main issues: (1) the legal framework regulating women’s participation in legislative elections in Indonesia, and (2) the implementation of these regulations by political parties in the legislative nomination process. This research employs a normative juridical method using a statute approach and an analytical approach. Data were obtained through an examination of the Constitution, statutory regulations, regulations issued by the General Elections Commission (KPU), and relevant academic literature. The findings show that the regulation of women’s participation in legislative elections is embedded in various legal instruments, such as Articles 28H and 28I of the 1945 Constitution, Law Number 7 of 2017 on General Elections, and KPU Regulation Number 10 of 2023. However, in practice, the implementation of these provisions continues to face several challenges, particularly relating to political party structures, entrenched patriarchal culture, and the limited institutional commitment to gender equality. It can be concluded that although the normative framework governing women’s participation is adequate, its implementation remains ineffective. Political parties require internal political reform, and stronger oversight from electoral management bodies is necessary to ensure that women’s representation is not merely formalistic but also substantive.